Implementasi Nilai Kepedulian Sosial Mahasiswa melalui Projek NARASI di Panti Asuhan Sunan Kalijaga - Sacralia Aurora Adila Ramadhana; Arma Tahsya Febriyanti; Diva Siska Amelia; Athira Khanaya Hud; Karenina Zulfa Qolby; Ghefira Amelia Aundra (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Children in orphanages represent a vulnerable group requiring special attention in emotional, social, and moral aspects. This study aims to implement students' social care values through the narasi Project (narasi aksi rasa asih dan inspirasi) at the Sunan Kalijaga Orphanage, Malang. The method employed was a social action approach integrated into the Civic Education course. The activity was conducted on March 10, 2026, involving eight foster children as the target partners. The program comprised a prophetic storytelling session as a character education medium, canvas painting and clay workshops to foster creativity, an ice-breaking session, congregational Maghrib prayers, iftar together, and symbolic cash donation handover. The results indicated that the or orphaned children responded enthusiastically to all activities, particularly the storytelling and creative sessions, reflecting improvements in self-expression, social interaction, and moral values. For the students, this project demonstrably enhanced empathy and social responsibility. Flexibility and adaptability in program implementation were identified as key success factors. In conclusion, the synergy of character education, creativity, and social action can create an inclusive and meaningful learning environment while strengthening civic values among university students.